Folk Tales & Advertising: A Competence Approach Applied to Little Red Riding Hood - Escalante Barrigón, Arturo (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
The educational legislation in Spain is based on the competences that students should develop throughout their school life. Therefore, teachers try to help students to interpret and understand the world around them in order to be able to manage in a successful way. The use of folk tales in the classrooms, questioned in recent years because of non-literary issues, makes intertextuality between folk tales and other means of communication accessible to those who have developed their literary competence. Through the ads related to Little Red Riding Hood, so popular in our culture, we may realise how relevant is to know this folk tale in order to understand all these advertising texts.